2010
DOI: 10.1021/ja909408q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Responses and Electrocatalysis at Single Au Nanoparticles

Abstract: Steady-state electrochemical responses have been obtained at single Au nanoparticles using Pt nanoelectrodes. A Au single-nanoparticle electrode (SNPE) is constructed by chemically immobilizing a single Au nanoparticle at a SiO(2)-encapsulated Pt disk nanoelectrode, which was previously modified by an amine-terminated silane. The Au SNPE has been characterized by transmission electron microscopy, underpotential deposition of Cu, and steady-state cyclic voltammetry. It has been found that the presence of a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
235
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(259 citation statements)
references
References 75 publications
9
235
0
15
Order By: Relevance
“…The same holds true for AuNP with a nominal diameter of 20 nm, although the rate of charge decay with respect to the scan number was considerably slower than for 4 nm AuNP ( Figure 3B). Also, the cathodic and anodic peak potentials measured for both 4 nm and 20 nm AuNP were shifted relative to the bulk gold oxidation ( Figure S4, Supporting Information).Such sizedependent AuNP oxidation potential shifts were observed in previous studies [11,12] using surface attached particles and suggested a theoretical model based on free energy changes with the metal surface area.…”
Section: Brsupporting
confidence: 73%
See 1 more Smart Citation
“…The same holds true for AuNP with a nominal diameter of 20 nm, although the rate of charge decay with respect to the scan number was considerably slower than for 4 nm AuNP ( Figure 3B). Also, the cathodic and anodic peak potentials measured for both 4 nm and 20 nm AuNP were shifted relative to the bulk gold oxidation ( Figure S4, Supporting Information).Such sizedependent AuNP oxidation potential shifts were observed in previous studies [11,12] using surface attached particles and suggested a theoretical model based on free energy changes with the metal surface area.…”
Section: Brsupporting
confidence: 73%
“…[12] Linker usage was avoided when AuNP are physisorbed using a drop-casting to screen printed [13] or glassy carbon electrodes, [14] that enabled to register particle size-dependent charge-transfer responses. A direct charge exchange between the freely diffusing nanoparticles and the ultramicroelectrode was also demonstrated recently, [14,16,17,18,19,20] despite low diffusion coefficients of nanoparticles in solution.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The landing experiments provided more information about transport processes and collision dynamics, the size distribution and concentration of NPs than electron transfer (ET) or catalytic activities. The problems in NP immobilization experiments [13][14][15] include difficulties in characterizing the geometry of the nanoelectrode/NP system, significant background current produced by the underlying electrode surface, and poorly defined NP shape if it is formed in situ by electrodeposition. …”
mentioning
confidence: 99%
“…Plasma enhanced chemical vapour deposition [11], chemical etching [5], self-assembly of gold nanoparticles have also been used to fabricate nanoelectrodes [12].…”
Section: Introductionmentioning
confidence: 99%